2020
DOI: 10.1029/2020gl090102
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Drivers of the Major Saharan Dust Storm in June 2020

Abstract: This study investigates the atmospheric dynamics of the major dust storm that occurred in June 2020 over the Sahara and during which dust clouds associated with the highest-on-record aerosol optical depths were transported towards the America. An anomalous atmospheric circulation pattern in the mid-latitudes, linked to a circum-global wavetrain, resulted in the development of a subtropical high-pressure system to the west of the Saharan Heat Low. This created a pressure dipole and generated anomalously strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 66 publications
2
45
1
Order By: Relevance
“…When the NASH became weaker and wandered back to south, the dust outflow region was dominated by the African Easterly Jet (AEJ), which carried the accumulated dust plume rapidly and maintaining its high concentrations from the coastal region toward the Caribbean Basin within four days, resulting in the extraordinary dust loading observed. Our results do not fully agree with what Francis et al (2020) found on the atmospheric drivers of the dust storm. For example, they argued that the development of a subtropical high off the coast of West Africa generated anomalously strong northeasterlies over four days and high dust loading in the eastern tropical Atlantic Ocean.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…When the NASH became weaker and wandered back to south, the dust outflow region was dominated by the African Easterly Jet (AEJ), which carried the accumulated dust plume rapidly and maintaining its high concentrations from the coastal region toward the Caribbean Basin within four days, resulting in the extraordinary dust loading observed. Our results do not fully agree with what Francis et al (2020) found on the atmospheric drivers of the dust storm. For example, they argued that the development of a subtropical high off the coast of West Africa generated anomalously strong northeasterlies over four days and high dust loading in the eastern tropical Atlantic Ocean.…”
Section: Discussioncontrasting
confidence: 99%
“…We also found that unique synoptic setting associated with anomalous NASH strength and position created the closed atmospheric circulations over West Africa and its adjacent coastal ocean for several days, which trapped the continuously emitted dust in the African coast. In addition, Francis et al (2020) found that the AEJ was much strengthened by the anticyclonic circulation associated with the anomalous sub-tropical high, which favored a rapid westward transport of dust toward the Americas. However, our estimated trans-Atlantic transport speed of 1000 km d -1 is more or less the same as the speed for the summertime dust events during 2003(Huang et al, 2010, suggesting that the strong AEJ in June 2020 was unlikely to be a major factor for the highest-in-record dust detected in the Caribbean Basin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The giant dust is likely important for the radiative effects, as well as for biogeochemical effects in the North Atlantic (Pabortsava et al, 2017;van der Does et al, 2018). In such an extreme case as the "Godzilla" dust storm over North Africa in June 2020 (Francis et al, 2020), the dust loading could be larger than that examined for this study, and our estimates of the warming effects might be conservative during such events.…”
Section: Discussionmentioning
confidence: 81%